Dicey's song - Voigt, Cynthia (New York : Aladdin Paperbacks, 2002)
Now that the four abandoned Tillerman children are settled in with their grandmother, Dicey finds that their new beginnings require love, trust, humor, and courage.
Sequel to: Homecoming.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
Booklist, April 2006.
Bulletin (Center for Children's books), September 2005.
Keywords: Brothers and sisters -- Juvenile fiction; Families -- Juvenile fiction; Grandmothers -- Juvenile fiction; Brothers and sisters -- Fiction; Family life -- Fiction; Grandmothers -- Fiction; Family life -- Fiction; Grandmothers -- Fiction; Siblings -- Fiction